2019
DOI: 10.1002/anie.201902779
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of α‐Trifluoromethyl Carboxylic Acids and Esters through Fluorocarboxylation of gem‐Difluoroalkenes

Abstract: A facile synthetic procedure for the preparation of α‐trifluoromethyl carboxylic acids and esters was achieved through multicomponent coupling reactions between gem‐difluoroalkenes, cesium fluoride, and carbon dioxide. The products were generated in moderate to excellent yields, and the synthetic utility of this method was demonstrated through the preparation of trifluoromethylated versions of popular nonsteroidal anti‐inflammatory drugs (NSAIDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 54 publications
0
24
0
1
Order By: Relevance
“…However, only up to 56:44 er was achieved in Feng and Loh's catalytic system after examining a variety of chiral ligands. Furthermore, Kobayashi [9] and Jiang [10] demonstrated that α‐CF 3 carbanion intermediate could be intercepted by CO 2 or bromoalkyne, furnishing the α‐CF 3 ‐carboxylic acids or α‐CF 3 ‐halides, respectively (Scheme 1 b). In 2018, α‐CF 3 carbocation intermediate was report by Wang [11] and Hu, [12] which generated from gem ‐difluoroalkenes with a F + source and applied to aminofluorination and fluoro‐hydroxylation, respectively (Scheme 1 c).…”
Section: Methodsmentioning
confidence: 99%
“…However, only up to 56:44 er was achieved in Feng and Loh's catalytic system after examining a variety of chiral ligands. Furthermore, Kobayashi [9] and Jiang [10] demonstrated that α‐CF 3 carbanion intermediate could be intercepted by CO 2 or bromoalkyne, furnishing the α‐CF 3 ‐carboxylic acids or α‐CF 3 ‐halides, respectively (Scheme 1 b). In 2018, α‐CF 3 carbocation intermediate was report by Wang [11] and Hu, [12] which generated from gem ‐difluoroalkenes with a F + source and applied to aminofluorination and fluoro‐hydroxylation, respectively (Scheme 1 c).…”
Section: Methodsmentioning
confidence: 99%
“…This strategy benefits from a reversible equilibrium as the addition of Freaction generates an ,,-trifluoromethyl anion 15, from which -fluoride elimination simply regenerates the gemdifluoroalkene, thus preventing the loss of substrate. [7][8][9][10][11][12][13][14][15] When using AgF, the metalated intermediate 17 can participate in Ag-or Pd-catalyzed processes in difunctionalization reactions (Scheme 2B). [16][17][18][19] Moreover, the use of electrophilic sources of fluorine, such as Selectfluor and NFSI can avoid anionic intermediates entirely (Scheme 2C).…”
Section: Two-electron Processesmentioning
confidence: 99%
“…This alternative route for synthesizing carboxylic acids could be employed with trifluoromethylated compounds [26,27]. These are an important group in the fluoro-alkyles group, and its carboxylic acid derivative has associated interest because it is a biologically active compound.…”
Section: Scheme 1 Electrochemical Carboxylation Processmentioning
confidence: 99%